Global financial crisis: the tasks ahead - Ahmed, Salehuddin (The Financial Express, 2014)
Dr Salehuddin Ahmed, former Governor of Bangladesh Bank, is now professor at BRAC University. He can be reached at: asalehuddin@gmail.com